Feasibility and conceptual design of non-invasive LF system for therapeutic applications - Wichai, Sangnark; Surapong, Pongyupinpanich; Chuchart, Pintavirooj; Nathupakorn, Dechsupa; Supaporn, Kiattisin (My University, 2014)
Since non-destructive therapeutic methods are taking into account in modem clinical therapy, this paper proposes the design concept of a configurable non-invasive radio frequency (RF) system for treatment applications. The system is designed based on the amplitude shift keying (ASK) technique and resonance RF of a marked cellular organism. At the resonance frequency, self-regulation mechanism of a cell is operated i.e. recovery and reconstruction. Carrier and low frequency are modulated systematically in order to perform particular resonance RF patterns. The modulated frequency is able to configure, to sweep and to radiate via spiral copper antenna in wide frequency spectrum from 0.1 MHz to 50 MHz with adjustable output power from 5-Watt to 50-Watt. Trial experiment with normal cancer cells at 1.52 MHz within 10 minutes reports that the cells are relatively respond to the RF frequency. The vitro testing results report that the generated RF signal effects to the development rate of cancer cells.